(untitled) (CIPEEX, 2026)
This study seeks to analyze the expansion of sports betting in Brazil and its social and psychological impacts, with an emphasis on the influence of digital marketing and easy access through online platforms. A narrative review of the literature is used, which is descriptive and cross-sectional in nature, based on articles published between 2020 and 2025 in databases such as CAPES, Scopus, SciELO, PubMed, Medline, and Google Scholar. The results indicate that, following changes in Brazilian regulations on fixed-odds betting, the sector in Brazil has grown significantly, generating billions in revenue. However, this growth has been accompanied by an increase in addictive behaviors, such as Gambling Disorder and Problem Gambling, which cause financial, social, and psychological harm, also affecting family members and close friends. In addition, aggressive marketing strategies and the cultural normalization of betting intensify vulnerability, especially among young people and university students. It is concluded that, although economically relevant, the expansion of betting requires more effective public policies and preventive measures that combine regulation, education, and mental health.